Direct Methanol Catalytic Fuel Cell, for Measuring Ethanol Contents in Pharmaceutical Tinctures - Tomassetti, Mauro; Angeloni, Riccardo; Marchiandi, Sergio; Castrucci, Mauro; Martini, Elisabetta; Campanella, Luigi (Current Analytical Chemistry, 2020)
Objective: In order to test real direct applicability for analytical purposes, a small and simple direct methanol (or ethanol) catalytic, enzymatic or non-enzymatic fuel cell (DMFC) was used for the analysis of ethanol-based pharmaceutical tinctures; a detailed experimental study was conducted on five different pharmaceutical tinctures available at drugstores. Results: The results obtained using both enzymatic and non-enzymatic devices were compared with those obtained by analyzing the same pharmaceutical samples with a conventional catalase biosensor. Finally, the results were compared with the nominal values provided by manufacturing firms. Conclusion: The correlations between the different experimental and nominal values considered were good in general or satisfactory and the applied statistical tests (f-test and t-test) were also very comforting. At the end of the study, the use of enzymatic DMFC proved to be better than non- enzymatic DMFC devices, because it requires shorter analysis times.
Keywords: catalytic reaction